Expanded transition spaces: the case of Garrwa - Gardner, Rod; Mushin, Ilana (Frontiers in Psychology, 2015)
Accounts of turn-taking in much of the CA literature have largely focused on talk which progresses with minimal gaps between turns at talk, longer gaps being found to be symptomatic of, for example, engagement in non-talk activities, or as indicators of some kind of trouble in the interaction. In this paper we present an account of turn-taking in conversations between Indigenous Australians where longer gaps are frequent and regular. We show that in sequences of such slow-paced conversation, gaps are not always treated as problematic, nor are they associated with non-talk activities that might inhibit talk. In such contexts we argue that there is less orientation to gap minimization, reflecting a lack of pressure for continuous talk. We also discuss qualitative differences in the nature of the gaps between turns in which there is a selection of next speaker, and those where no next speaker has been selected. Finally we consider whether such talk is a feature of Indigenous Australian conversation, or a more widespread practice.